Silver nanoparticles synthesised with red betel leaf (Piper crocatum) extract as a photosensitiser for inactivation of Escherichia coli and Staphylococcus aureus - Astuti, Suryani Dyah; Karren, Damita; Susilo, Yunus; Yaqubi, Ahmad Khalil; Zaidan, Andi Hamim; Nasrul Anuar Abd Razak (Penerbit Universiti Kebangsaan Malaysia, 2025)
Infectious diseases caused by Escherichia coli and Staphylococcus aureus are major health concerns in Indonesia, exacerbated by antibiotic resistance and biofilm formation. This study explores the use of betel leaf-synthesised silver nanoparticles (AgNPs) combined with red laser irradiation to enhance antimicrobial effectiveness against these resistant bacteria. The study included four groups: a control group (T0) without laser irradiation, E. coli groups (A1 and A2), and S. aureus groups (A3 and A4) treated with varying concentrations of AgNPs and irradiated with a 665 nm diode laser. The photosensitiser group (A2 and A4) received AgNPs synthesised from red betel leaf extract (AgNPs-Pc), followed by a 10-min incubation. The samples were then irradiated at four different times: 90, 120, 150, and 180 min, using a laser with a wavelength of 665 nm to evaluate the antimicrobial effects. The findings showed that AgNPs-Pc combined with a red laser significantly reduced E. coli growth compared to the control group without photosensitiser. For S. aureus, growth occurred after irradiation without photosensitiser (PS). Irradiation of S. aureus with AgNPs-Pc at concentrations of 1 mM, 1.5 mM, and 2 mM for 150 s resulted in bacterial death reductions of 89.74%, 91.24%, and 89.05%, respectively. The effective inactivation of E. coli was 87.29 ± 2.68% at an energy density of 22.68 J/cm². S. aureus required a higher energy density of 37.80 J/cm² for 91.24 ± 2.76% inactivation. This study shows that red betel leaf extract-synthesised silver nanoparticles combined with red laser irradiation effectively combat antibiotic-resistant E. coli and S. aureus.